Fragility Fracture Network Position on Unrestricted Weight-Bearing After Hip Fracture Surgery - Ruqayyah Turabi MSc; Frede Frihagen PhD; Rhona McGlasson MBA; David Wyatt PhD; Alex Trompeter PhD, FRCS; Lauren Beaupre PhD; Luiz Fernando Cocco PhD; Matthew Costa PhD; José Luis Dinamarca-Montecinos PhD, MSc; Juan Carlos Viveros-García MD; Jae-Young Lim MD, PhD; Joon-Kiong Lee FRCS; et al. (Geriatric Orthopaedic Surgery & Rehabilitation)
Objectives This position paper from the Fragility Fracture Network (FFN) responds to the observed global variation in weight-bearing prescriptions after hip fracture surgery in older adults. Methods The paper summarises current guidelines and evidence regarding unrestricted weight-bearing after hip fracture surgery. Results The synthesis of available evidence supports the endorsement of unrestricted weight-bearing after surgery to enhance patient outcomes. Conclusion The FFN endorses unrestricted weight-bearing and recommends healthcare professionals, institutions, and policymakers re-evaluate practices favouring limited or non-weight-bearing prescriptions and establish a standardised system for monitoring and auditing, with clear justification and documentation of any restrictions.